Assuring materials availability during the production transfer process: Critical characteristics of the materials planning environment. Issue 3 (1st April 2014) - Fredriksson, Anna; Wänström, Carl; Medbo, Lars
Abstract : Purpose: – The materials planning (MP) environment sets the prerequisites for the MP process. Before and during production transfer and start-up (PTS) supply chain uncertainty of the MP environment increases, as the company goes from a known to an unknown situation. The purpose of this paper is to describe the impact of the MP environment on the MP process before and during PTS. Design/methodology/approach: – A conceptual framework describing the MP environment before and during PTS is developed and applied to one case of outsourcing from Sweden to China. The framework is based on a literature review and further evaluated by both researchers and managers. Findings: – A conceptual framework describing the dynamic MP environment before and during PTS has been developed compared to previously static MP environments descriptions. In addition, this framework proved to be useful in analysing the importance of various characteristics of the MP environment before and during PTS. Practical implications: – The study highlights the importance of a proactive approach to materials availability when transferring production. The conceptual framework developed here can be used as a checklist to identify the characteristics of the MP environment that are most important to ensuring materials availability. Originality/value: – The paper highlights the PTS when outsourcing, a substantial time frame with a large impact on success. This is an important contribution, given the focus of previous outsourcing research on strategic issues. Further, the paper demonstrates the differences between static and dynamic MP environments.